Iraq's relations with the European Union after 2003 (Journal of the College of Basic Education, 2023)
The relation between Iraq and EU goes back to the begging of the 20 th century since the establishment of the independent of Iraq 1921 , but this relation face a difficult times after Saddam Hussein occupied Al – Kuwait 1990-1991. It was obvious after 1990 that this relations was in continue but with a very few countries under the observer of the UN program oil instead food and medicine.It was clear there were no political or contractual relations between the EU as a group and Iraq after the Gulf War, but after the US operations inside Iraq the political regime was changed in Iraq and it was reflected on his foreign policy and relations with the International community. At the beginning and after 2003 EU members opposed the US occupation of Iraq , later they divided over the issue of attacking Iraq but at the end EU support US for attacking Iraq under the pretext of weapons of mass destruction and it was strongly clear when the majority of the UN security council member whose have the veto right ( EU members States) and the US were same interests and political directions over Iraq issue